PENGARUH KEPUASAN KERJADAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION KARYAWAN PADA PT MARTINDO FINE FOODS DI KOTA BATAM - adrias, adrias; Rasiman, Suhardi (SCIENTIA JOURNAL, 2021)
This research is intended to analyze the influence of job satisfaction and organizational commitment on turnover intention at PT Martindo Fine Foods.The technique used in collecting data used in this research is the distribution of questionnaire using purposive sampling method, whereby the population and sample used in this research are all the employees working for PT Martindo Fine Foods amounting toa total of 120 respondents. This research uses two independent variables which are job satisfaction variable and organizational commitment variable.This research uses data analysis methods such as validity test, reliability test, classic assumption test,multiple linear regression analysis, determination coefficient test, and hypothesis test. The result of this research show that job satisfaction variable does have influence and is significant towards the turnover intention of employees, so is the organization commitment variable does have influence and is significant towards the turnover intention of employees. Furthermore, job satiscation and organizational commitment variable simultaneously does haveinfluence and significant towards the turnover intention of employees of PT Martindo Fine Foods. Variables in this research have an influence44,8% towards the turnover intention of employees. The rest 55,2% are influenced by other variables coming from outside of this research.